Associations between hospitalist physician workload, length of stay, and return to the hospital. Issue 6 (6th June 2022) - Djulbegovic, Mia; Chen, Kevin; Cohen, Andrew B.; Heacock, Daniel; Canavan, Maureen; Cushing, William; Agarwal, Ritu; Simonov, Michael; Chaudhry, Sarwat I.
Abstract: Background: Hospitalist physicians' workload–the total number of patients they care for daily–is rising in the U.S. Hospitalists report that increased workload negatively affects patients care. Objective: Measure the associations between hospitalist physicians' workload and clinical outcomes. Design, Settings, and Participants: Observational study, using electronic health record (EHR) data, of adults hospitalized on the hospitalist service at Yale‐New Haven Hospital from 2015‐2018. Main Outcome and Measures: We defined hospitalists' workload as the number of patients they cared for on the first full hospital day of a given patient's encounter. We used multilevel Poisson and logistic regression to examine associations between workload and length of stay (LOS), return to the Emergency Department (ED), and readmission. We adjusted for sociodemographic factors, patient complexity and severity of illness, and weekend admission (for LOS) or discharge (for ED visits or readmission). Results: We analyzed 38, 141 hospitalizations. Median patient age was 64 years (IQR 51‐78 years), 53% were female, and 34% were nonwhite. Mean workload was 15 patients (SD 3 patients; range 10‐34 patients). LOS was prolonged by 0.05 days (95% CI 0.02, 0.08; p(0.001) when comparing the 75th workload percentile (16 patients) to the 25th workload percentile (13 patients). There were no associations between workload and ED visits or readmission within 7 and 30 days. Conclusions: There was a statistically significant but modest relationship between workload and LOS; workload was not associated with ED visits or readmissions.Given clinical reports of the deleterious effects of increased hospitalist workload, there is a need for prospective research assessing a range of outcomes, beyond those measurable in contemporary EHR data.